ANALISIS SEMIOTIK CHARLES SANDERS PEIRCE TERHADAP LOGO PROVINSI GORONTALO - Siska Udilawaty; Apsari Dj.Hasan (STEKOM PRESS, 2022)
This study discusses the meaning contained in the logo of the Province of Gorontalo in semiotic analysis. Logo is the identity of an institution that represents the history and culture of the institution while semiotics is the science of reading signs both verbally and visually, visual forms make the vision and mission as well as identity reflected in a logo. Just like the regional logo of Gorontalo Province which has various meanings of signs and symbols that reflect the area, for example, the Padi and cotton symbols are inspired by the city government logo which means depicting prosperity and others. There is also an oval pattern in the logo taken from the eggs of the Maleo bird, which is endemic to Gorontalo. There is the fort of Otana and pictures of books taken from our philosophy